(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The implement of the Suvarna Jayanti Revenue Campaign it has been possible to successfully deal with the problems related to the needs of common citizens through this campaign. Also along with the daily work of the people this campaign has been used to settle the pending work in front of everyone and create transparency in the revenue work. In the background of increasing population, increasing urbanization, increasing industrialization, there has been an increase in the work of the revenue department. By well-planned use of information technology and proper management of the growing work has become possible. The true credit of such a people-oriented campaign. It goes to Balasaheb Thorat as it is a matter of pride for us that this campaign has taken Maharashtra to a different height due to his positive attitude and approach towards this campaign.